SETTLEMENT OF CRIMINAL ACTS IN THE MILITARY JUSTICE SYSTEM THROUGH A RESTORATIVE JUSTICE APPROACH - Zarkasi Zarkasi; Indra Gunawan Purba; Ahmad Rusly Purba (Jurnal Ilmiah METADATA, 2025)
Restorative justice in the settlement of crimes in the Military Court is an approach that prioritizes the restoration of relationships between perpetrators, victims, and institutions through dialogue and mediation. The results of the study show that the application of the concept of restorative justice in the settlement of criminal acts in the Military Justice system is applied through mediation to resolve conflicts by involving perpetrators, victims, and related parties to seek a peaceful settlement that focuses on restoring the original state, not just retaliation. The harmonization of law in the implementation of restorative justice in the settlement of criminal acts in the Military Justice system faces a number of challenges and opportunities, mainly due to the unique characteristics of the military justice which is oriented towards discipline and hierarchy. This harmonization effort involves an adjustment between the concept of restorative justice that focuses on restoration and the military justice system that is retributive.